Position of Foundation Assets from State Assistance - Mohammad Fahdi; Amin Purnawan (Sultan Agung Notary Law Review, 2020)
The existence of a foundation in the community to achieve various activities, aims and objectives in the social, religious and humanitarian fields has developed rapidly and has more diverse features. However, there are various interpretations of the substance of the Law on Foundations in society, which can lead to uncertainty and legal order. In this connection, a foundation is a legal entity consisting of separated assets of the founder. In addition, the source of the foundation's wealth can be obtained from other sources. A foundation is a legal entity consisting of separated assets of the founder. In addition, the source of the foundation's wealth can be obtained from other sources. Based on the Foundation Law, it is stated that the sources of the Foundation's assets can also be obtained from: donations or assistance that are not binding, waqf, grants, testament grants, and other acquisitions that do not conflict with the articles of association or the prevailing laws and regulations. Donations or non-binding assistances are defined as voluntary donations or assistance received by a foundation, whether from the State, the community or from other parties. This research was conducted to analyze problems arising from the position of the foundation's assets originating from state assistance and to find solutions to the problems that arise. The approach method used in this research is normative juridical which is descriptive-analytical in nature. Primary data is obtained using field research methods, while secondary data is obtained through library research. The collected data were analyzed qualitatively. The results of this study indicate that the management of the foundation is still influenced by the bureaucratic structure when viewed from the composition of the personnel of coaches, administrators and supervisors consisting of former local government officials and the Ministry of Religion of Cirebon Regency.